Anti-corruption models and experiences: The case of the Western Balkans - Enrico Carloni; Diletta Paoletti (FrancoAngeli, 2022)
The challenge of fighting corruption is strategic at a global and European level, and the inadequacy of the repressive and penal response alone has now been evidenced: corruption must not only be fought, but understood, and preventive administrative measures must be taken. Anti-corruption is not an issue that concerns only the judiciary branch, the legal system, and police authorities, but it is, above all, a challenge for society and institutions as a whole. And it is a challenge to be transformed, in particular, into a change in administrations and institutions, in their way of organizing and operating. This volume the result of the Project 'Administrative Prevention through Targeted Anti-corruption MODels for candidate countries' - APTAMOD, co-funded by the European Union's HERCULE III programme, which has conducted comparative law studies and high-profile research activities in the field of administrative prevention of corruption, with specific focus on Albania, Montenegro, North Macedonia and Serbia.
Keywords: 330